[tex]\text {Hi There! The answer to your problem is}[/tex]
[tex]\fbox {x=-3/13}[/tex]
[tex]\text {Your 1st Step will be to Simplify the Equation}[/tex]
[tex]\text {-5x+3=8x+9+-3}[/tex]
[tex]\text {-5x+3=(8x)+(9+-3) (Combine Like Terms)}[/tex]
[tex]\text {-5x+3=8x+6}[/tex]
[tex]\text {The Next Step is to Subtract 8x}[/tex]
[tex]\text {-13x+3-3=6-3}[/tex]
[tex]\text {-13x=3}[/tex]
[tex]\text {The Final Step is to Divide by -13}[/tex]
[tex]\text {-13x/13=3/-13}[/tex]
[tex]\text {x=-3/13}[/tex]
[tex]\text {Best of Luck!}[/tex]
[tex]\text {-LimitedX}[/tex]